Diferencias sociodemográficas entre usuarios de inhalables, usuarios de otras drogas y adolescentes no consumidores en una muestra mexicana de estudiantes - María Elena Medina-Mora; Claudia Rafful; Jorge A. Villatoro Velázquez; Natania Oliva Robles; Marycarmen Bustos Gamiño; Midiam Moreno (Revista Internacional de Investigación en Adicciones, 2015)
Introduction: inhalants like glue, paint thinner, and other petroleum-derived substances are one of the most utilized substance groups among Mexican teenagers. Recent studies have found that, along with marijuana, inhalants are the preferred substance of abuse among youth.